The nature of glossolalia in the neo-Pentecostal churches in Nigeria - Solomon O. Ademiluka (Verbum et Ecclesia, 2024)
Glossolalia has been a major divisive doctrine in the Christendom, as some Pentecostals claim that it is proof of being a real Christian. This article examined the extent to which tongues-speaking in the neo-Pentecostal churches in Nigeria conforms to New Testament (NT) teaching. It employed narrative criticism and the phenomenological approach. The essay found that glossolalia appeared in the NT in both human and unintelligible languages. As the gift caused disorderliness in the Corinthian church, Paul says it is desirable but should not be allowed to disrupt worship. During worship, there should not be more than three people speaking in tongues, and they should do it in turn. Most importantly, if there is not an interpreter, there should be no tongues-speaking at all. The work further discovered that in the Nigerian neo-Pentecostal churches, it is the unintelligible form of glossolalia that is predominantly practised, and usually without interpretation, thereby contradicting Paul’s order. Moreover, the gift is being feigned by many to prove that they are born-again. In terms of its nature and conduct, therefore, glossolalia in the neo-Pentecostal churches in Nigeria is more of a deliberate practice than a continuation of the NT practice.